Community-Based Education Model to Empower Communities in Utilizing Local Potential (Analysis Study on Community-Based Learning Centers in Lampung Province) - Anwar, Syaiful; Shawmi, Ayu Nur (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2023)
This research stems from the discussion about developing and implementing the concept of community education, which is essentially a form of democratization of education through expanding educational services for the benefit of the community. The problem formulation is (1) What local potential is available around PKBM to be utilized in community-based education activities in Lampung Province? (2) What is the level of community empowerment after attending community-based education using the available local potential? (3) What is the conceptual model of community-based education to civilize the community in utilizing local potential? This research aims to utilize the local potential available around PKBM in community-based education activities in Lampung Province, determine the level of community empowerment after attending community-based education by utilizing local potential, and find a conceptual model of community-based education to empower communities in utilizing local potential. The research approach used in this study is qualitative. The analysis showed that the most dominant advantages of local potential in Bandar Lampung city are the availability of educational institutions and services, complete infrastructure, development of information systems and technology, the availability of quality human resources, and the development of arts and culture. For that, the local potential of Bandar Lampung city is excellent in developing technology and culture. Generally, the average level of community empowerment in the Lampung region is in the good category. This condition has the potential to continue to improve community empowerment through an education process based on local potential.